2014
DOI: 10.1021/es405029y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activated Carbon Cathode Performance for Microbial Fuel Cell by Blending Carbon Black

Abstract: Activated carbon (AC) is a useful and environmentally sustainable catalyst for oxygen reduction in air-cathode microbial fuel cells (MFCs), but there is great interest in improving its performance and longevity. To enhance the performance of AC cathodes, carbon black (CB) was added into AC at CB:AC ratios of 0, 2, 5, 10, and 15 wt % to increase electrical conductivity and facilitate electron transfer. AC cathodes were then evaluated in both MFCs and electrochemical cells and compared to reactors with cathodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(89 citation statements)
references
References 34 publications
(87 reference statements)
2
86
0
Order By: Relevance
“…Fluorinecontaining resin materials such as polytetrafluoroethylene (PTFE) are widely used as a binder, as they have excellent chemical and thermal resistance and are best known for their binding properties. PTFE is widely used as a binder for the fabrication of cathode for energy storage, particularly in microbial fuel cell [13][14][15][16] and capacitor/supercapacitor [17,18]. On one hand, Zarei, et al [19] developed carbon nanotube-PTFE cathode for dye removal under several different operating conditions, while on the other hand, Park, et al [20] prepared activated carbon-PTFE electrode sheet for desalination.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorinecontaining resin materials such as polytetrafluoroethylene (PTFE) are widely used as a binder, as they have excellent chemical and thermal resistance and are best known for their binding properties. PTFE is widely used as a binder for the fabrication of cathode for energy storage, particularly in microbial fuel cell [13][14][15][16] and capacitor/supercapacitor [17,18]. On one hand, Zarei, et al [19] developed carbon nanotube-PTFE cathode for dye removal under several different operating conditions, while on the other hand, Park, et al [20] prepared activated carbon-PTFE electrode sheet for desalination.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that i) surface chemistry, 22 ii) temperature treatment, 19,25 iii) pressure applied, 19 iv) AC loading, 22 v) content of binder (e.g. PTFE), 22 vi) addition of carbon black, 26 affect the cathode performances and the MFC output significantly. AC seems to be the cheapest and efficient solution to adopt for scaling up MFCs.…”
mentioning
confidence: 99%
“…After that, 12.6 µL of PTFE (Sigma-Aldrich, Cd Mexico, Mexico) to 60% and 233.3 µL of deionized water were added to the vial, followed by a 5 min ultrasound to form a paste. This paste was placed on the SSME as shown in Figure 1b [31]. The support was constructed with PVC as shown in Figure 1 where (c) serves as the base for the structure of the electrode, (d) is placed on top, then the Nafion ® membrane and electrode are placed so that the AC-CB face is on the membrane, then the electrode is pressed by placing (e) and finally the system is closed with (f).…”
Section: Floating Air Cathodementioning
confidence: 99%
“…Therefore, this performance has been limited mainly by the oxygen reduction reaction at the aqueous cathode due to the poor kinetics of the reaction at neutral pH, which is why some authors propose the use of aerated cathodes for BMFC, where the oxygen flow is 3.7 times higher than in an aqueous cathode [10,16,23,[28][29][30]. These air cathodes are composed of three layers: the first is the collector in which electrons are received from the anode through the external circuit, the second is the catalyst which promotes the reduction reaction at the cathode and the third layer is the diffuser, which allows the reaction, improving the conditions of evaporation and substrate consumption [18,31].…”
Section: Introductionmentioning
confidence: 99%